(untitled) (IF-Sophia: revista eletrônica de investigações Filosófica, Científica e Tecnológica, 2018)
Whenever people think of war, they often reflect on the tragic loss of human life. They seldom consider the loss and damage caused to nature. War, since the beginning of its history, has never been close to the happiness, tranquillity and security of humanity and even the spectrum of war that causes people to be traumatised. The activities that correlate the war that affected life and the environment are productions, testing an explosion of nuclear weapons. Land and naval bombers, landmines, and Depredation, defoliation and toxic pollution. An example, the war that took place in Southeast Asia after World War II in 1975 on the invasion of Indonesia on the island of Timor. Indonesian forces moved hundreds of thousands of people into concentration camps, where they were famine and disease. Indonesian aircraft bombers spread chemical agents throughout the island, where they resulted in various diseases that affected animals and the population. Although many people die in lack of access to food. The land was burned along with animals intended for farming.